Vinegar and weight loss in women of eighteenth-century France: a lesson from the past - Almenara, Carlos A. (2020)
This short note reports the eighteenth-century account of Mademoiselle Lapaneterie, a French woman who started drinking vinegar to lose weight and died one month later. The case, which was first published by Pierre Desault in 1733, has not yet been reported by present-day behavioural scholars. Similar reports about cases in 1776 are also presented, confirming that some women were using vinegar for weight loss. Those cases can be conceived as a lesson from the past for contemporary policies against the deceptive marketing of potentially hazardous weight-loss products.